PRP and Cotton-Like β-TCP/PLGA Fibers Enhance Bone Repair in Osteoporotic Vertebral Defects via Macrophage Modulation in Rats - Shimizu, Yuichi; Nagae, Masateru; Tonomura, Hitoshi; Ishibashi, Hidenobu; Takeura, Nobuaki; Morita, Takahiro; Sakata, Munehiro; Yamada, Shunji; Tanaka, Masaki; Takahashi, Kenji (Acta histochemica et cytochemica, 2025)
This study assessed the effectiveness of a combination of platelet-rich plasma (PRP) and β-tricalcium phosphate/polylactic-co-glycolic acid (β-TCP/PLGA) fibers in the treatment of osteoporotic vertebral defects in rats. Seventy-two female Sprague-Dawley rats subjected to ovariectomy to induce osteoporosis were divided into three groups to receive different treatments for critical bone defects created in the lumbar vertebrae. The PRP group received β-TCP/PLGA fibers infused with PRP, the control group received no material, and the other group received the same fibers infused with phosphate-buffered saline (PBS). Over a period of 12 weeks, bone regeneration, macrophage differentiation, and inflammatory responses were evaluated histologically. Compared to the PBS group, the PRP-treated group demonstrated significantly enhanced early stage bone formation, increased expression of osteogenic markers, and a favorable shift in macrophage activity from the M1 inflammatory phenotype to the M2 healing phenotype. These outcomes suggest that the combination of PRP and β-TCP/PLGA fibers not only effectively promotes bone repair under osteoporotic conditions but also modulates the immune response to facilitate better healing, indicating its potential as a beneficial surgical intervention for osteoporotic vertebral fractures.